(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Arsha is a common anorectal disease so associated with bleeding per anum . It can be compared toHaemorrhoids accoding to modern science. Haemorrhoids are dilated veins in the anal canal. Through allthe modern modalities of treatment in haemorrhoids are universally accepted but all have some or otherlimitations. In Ayurveda various measures have been mentioned for the management of Abhyantar Arsha ,among which lepa karma is one of them . Various study have been done on the application of various lepaso prepared have been conducted depending upon the sign and symptoms. In this study the effectivenessof Pippalyadi and Suranadi ointment were compared which were so mentioned in bhaishajya ratnawali.In this preset researnch work efforts were made to provide the treatment which is non-invasive, easy toimplement, effective and not need any hospitalization. In this study 30 patients of Arsha were selected as percriteria of selection randomly irrespective of religion, socio-economic status and were divided in 2groupsof 15 patients each. Group-A was treated with Pipplyadi oitment advised for 15 days twice a day as localapplication. Group-B allotted Suranadi Ointment given twice a day for local application for 15 days andaccordingly the result were assessed. Pippalyadi and Suranadi ointment were prepared according to thetexts and the ointment was used for local application on the patients of Arsha. Lastly, it was concluded thatboth the ointments have shown significant results in the patients without any side effects.